Knowledge and Eating Patterns of Fishermen With Hypertension In The Puskesmas Wulla Waijelu - Windy Putri Perdina Yusuf; Yuneti Octavianus Nyoko (Poltekkes Kemenkes Kupang, 2019)
Background: People with hypertension in the last 3 years in Wulla Waijelu Region continued to increase, in 2015 as many as 210 people, in 2016 there was 273 people and in 2017 was 431 people. Most of the people the Puskesmas Wulla Waijelu are fishermen. The purpose of this study was to describe the knowledge and eating patterns of fishermen with hypertension in the Puskesmas Wulla Waijelu. Method: This type of research is an analytical study with a descriptive study design. Variables of knowledge and eating patterns to hypertension. Data collection with questionnaire instrument. Data analysis was univariat. Results: Characteristics of 30 fishermen showed that all were male, aged 30 to 51 (30%) and had education at the elementary, junior high and high school levels of 27%. The results of the univariate analysis showed that the fishermen had poor knowledge about hypertension as many as 16 people (53%) and most of the fishermen's had poor eating as many as 26 people (87%). Suggestion: Fishermen Active to looking for information about health problems, especially about hypertension and also health workers need to improve information about hypertension and provide counseling where fishermen gather when they finish fishing.